NEW ON THE NARRATIVE STRATEGIES IN “THE CAPTAIN’S DAUGHTER” BY ALEXANDER PUSHKIN - Olga V. Bogdanova (Alfred Nobel University Journal of Philology, 2019)
The article analyzes the narrative strategies of Pushkin’s “The Captain’s Daughter” (1836) and attempts to rethink the traditional scientific understanding of the character of the narrative in Pushkin’s historical text. Various approaches to narrative strategies are revealed and considered in the work, various types of narrative intentions differentiated by the type of subjectivity / non-subjectivity of the narrator, by the degree of objectivity / subjectivity of the estimated axiology, by the orientation of the narrator to the reader’s perception, the degree of emotional coloration of the speech of various characters connected to the narrative are analyzed. The article offers a new look at the system of storytellers in Pushkin’s “The Captain’s Daughter”. If traditionally the narrator Peter Grinev was recognized as the only narrator who gives the reader an objective idea of the events of the Peasant war of 1773-1775 under the leadership of Yemelyan Pugachev, then this article proposes to adjust this approach and consider not “one”, but “binary” systems of storytellers: including the narrator Peter Grinev and the unnamed publisher, whose points of view are consciously differentiated by Pushkin and do not always coincide. The article shows that Pushkin consciously uses the technique of “author’s disguise”, when the main narrative is not the writer himself, but the direct participant in the events of the Pugachev uprising — Peter Andreevich Grinev. Meanwhile, along with this, the work focuses on the fact that Pushkin consciously introduces a non-contoured face of the publisher to the text of the novel, who has the right to intervene in the text of Grinev and correct it, introducing ambiguity of perception, ambiguity of assessments, revealing an ironic perspective, compromising the “objectivity” of the main narrator. The article shows how at different levels of the text, the position of the narrator Grinev and the position of the publisher (the author) differ, the level of awareness of the characters does not match, generating stereoscopic images of the event, bringing the ambiguity of perception of the same circumstances, situations, episodes. The novelty of the work lies in the fact that for the first time in the text of “The captain’s daughter” not one narrator (traditional aspect of the study), but two narrators: naive gullible Peter Grinev (narratorteller) and “impersonal”, but endowed with its own position publisher, legally intervening in the Grinev text at the level of choice of the title of memoirs (the title of the novel), and at the level of the main division of the diary, at the choice of epigraphs to the whole novel and to its separate parts-chapters. As shown in the work, the emotional-evaluative layer of perception of the narrator and the publisher, as a rule, do not coincide, at its intersection revealing the position of the writer Pushkin. The study is based on a set of different methods of analysis of literary text: historical method, biographical, comparative and poetical method, which allows to carry out the nuances of the writer’s tactical moves, to implement and sustain the strict logic of scientific research.